Validation of a Portable Ionized Calcium Detection Device and Changes in the Ionized-to-Total-Calcium Ratio in the Blood of Postpartum Holstein Cows - Zhongming Cao; Yan Zhao; Bo Zhang; John P. Kastelic; Mengjie Hu; Jia Cheng; Mingchao Liu; Jian Gao (Animals)
The calcium requirements of dairy cows increase dramatically soon after calving, and many cows have subclinical hypocalcemia, adversely affecting health and performance. Traditional laboratory tests for calcium are complex and not easily adapted to rapid point-of-care applications. The objectives were to evaluate a portable iCa testing device, Horiba LAQUAtwin Ca-11C, for measuring ionized calcium (iCa) in the whole blood of dairy cows and to investigate the iCa-to-total-calcium (tCa) ratio in blood collected from dairy cows within 9 days after calving. This study was conducted on two large dairies in northern China. First, blood samples were collected from 246 cows within 3 days after calving, and whole-blood iCa concentrations were measured with a Horiba LAQUAtwin Ca-11C and Abbott i-STAT 1. In addition, 885 blood samples were collected from 102 dairy cows between calving and 9 days postpartum, with iCa concentrations measured using a Horiba LAQUAtwin Ca-11C and tCa concentrations determined by a fully automated biochemical analyzer. The Horiba LAQUAtwin Ca-11C and Abbott i-STAT 1 had significant consistency in the measurement of ionized calcium concentration in whole blood (the frequency of differences between the measured values was within ±20% of the average, reaching 95.53%), and the measurement results of the two instruments were correlated (Deming regression analysis R2 = 0.87). This implied the potential application of the Horiba LAQUAtwin Ca-11C as a simplified device for measuring iCa in dairy farms for on-site testing. Within the first 9 days after calving, the ratio of ionized calcium to total calcium fluctuated but overall remained within the range of 44.2 to 47.22%. Furthermore, significant variations in the ratio among individual cows indicated that individual differences and physiological states of cows affected calcium metabolism. This study identified the potential to use the Horiba LAQUAtwin Ca-11C for point-of-care testing on dairy farms. Nevertheless, the impacts of factors such as health status and individual cow differences on the ratio of ionized calcium to total calcium still require further investigation.